`Injury prevention versus performance`: has the time come to mandate the use of mouthguards in all contact sports? - Ahmed, I.; Fine, P. (BMJ Open Sport & Exercise Medicine, 2021)
Mouthguard use continues to be a hotly debated issue in the domain of contact sports. Regulations from sports governing bodies on wearing mouthguards and attitudes towards their use from athletes vary significantly across `at-risk sports`. We explore how recent advances in sports dentistry have led to the widespread availability of new customisable mouthguards and whether their use may impact athletic performance, reduce orofacial trauma or sport related concussion. We also discuss whether `no mouthguard, no play` policies designed to mandate their use may help to promote a culture of safe participation in contact sport.